Breaking Free from Cobalt Reliance in Lithium-Ion Batteries - Gourley, Storm William D.; Or, Tyler; Chen, Zhongwei (Elsevier, 2020)
The exponential growth in demand for electric vehicles (EVs) necessitates increasing supplies of low-cost and high-performance lithium-ion batteries (LIBs). Naturally, the ramp-up in LIB production raises concerns over raw material availability, where constraints can generate severe price spikes and bring the momentum and optimism of the EV market to a halt. Particularly, the reliance of cobalt in the cathode is concerning owing to its high cost, scarcity, and centralized and volatile supply chain structure. However, compositions suitable for EV applications that demonstrate high energy density and lifetime are all reliant on cobalt to some degree. In this work, we assess the necessity and feasibility of developing and commercializing cobalt-free cathode materials for LIBs. Promising cobalt-free compositions and critical areas of research are highlighted, which provide new insight into the role and contribution of cobalt.
Keywords: energy storage; energy materials